Combining single-cell RNA sequencing and network pharmacology to explore the target of cangfu daotan decoction in the treatment of obese polycystic ovary syndrome from an immune perspective - Liu, Danqi; Wei, Chaofeng; Guan, Lu; Ju, Wenhan; Xiang, Shan; Lian, Fang (Frontiers in Pharmacology, 2024)
Background: Polycystic ovary syndrome (PCOS) is a heterogeneous gynecological 12 endocrine disorder linked to immunity. Cangfu Daotan Decoction (CFDT), a classic 13 Chinese medicine prescription, is particularly effective in treating PCOS, specifically 14 in patients with obesity; however, its specific mechanism remains unclear. 15 Methods: Part 1: Peripheral blood mononuclear cells were collected on egg retrieval 16 day from obese and normal-weight patients with PCOS and healthy women undergoing 17 in vitro fertilization (IVF)-embryo transfer. Next, scRNA-seq was performed to screen 18 the key genes of bese patients with PCOS. Part 2: Active ingredients of CFDT and 19 obesity-related PCOS targets were identified based on public databases, and the binding 20 ability between the active ingredients and targets was analyzed. Part 3: This part was a 21 monocentric, randomized controlled trial. The obese women with PCOS were 22 randomized to CFDT (6 packets/day) or placebo, and the healthy women were included 23 in the blank control group (43 cases per group). The clinical manifestations and 24 laboratory outcomes among the three groups were compared.